Blended Learning Berwawasan Literasi Digital Sebagai Upaya Memenuhi Tantangan Pembelajaran Abad 21 - Hanik Khusnul Khotimah; Isykarima Amalia Vita Noor Izzaty (Proceedings Series of Educational Studies, 2023)
Abstract: Learning in the 21st century is inseparable from advances in science, technological developments, and digital information. The standard for 21st century or digital century schools for teachers and students is the application of technology in learning. Digitalization of technology in the world of education has resulted in innovations in learning activities, learning resources, and learning models. Implementation of learning with a Blended Learning model can optimize students' digital literacy which will affect the increase in the quality of learning. So far, digital literacy is only known through social media which contains various information, but has not been optimized to support improving the quality of learning. The method used in this research is literature study by relying on various literature to obtain data and using a qualitative approach. As the forefront of education, teachers need to continue to adapt and develop learning strategies to produce quality learning outcomes. The concept of digital literacy in a proportionally developed Blended Learning setting can be considered as an effort to improve the quality of learning in the 21st century.Keywords: Blended Learning, digital literacy, 21st century learningAbstrak: Pembelajaran abad 21 tidak terlepas dari majunya ilmu pengetahuan, perkembangan teknologi, dan informasi digital. Standar untuk sekolah abad 21 atau abad digital bagi guru dan peserta didik adalah dengan penerapan teknologi dalam pembelajaran. Digitalisasi teknologi dalam dunia pendidikan telah mengakibatkan adanya inovasi dalam kegiatan pembelajaran, sumber belajar, dan model pembelajaran. Implementasi pembelajaran dengan model Blended Learning dapat mengoptimalkan literasi digital peserta didik yang akan berpengaruh terhadap meningkatnya kualitas pembelajaran. Selama ini literasi digital hanya dikenal melalui media sosial yang memuat berbagai informasi, namun belum dioptimalkan untuk mendukung peningkatan mutu pembelajaran. Metode yang digunakan dalam penelitian ini adalah studi pustaka dengan mengandalkan berbagai literatur untuk mendapatkan data dan menggunakan pendekatan kualitatif. Sebagai garda terdepan pendidikan, guru perlu terus beradaptasi dan mengembangkan strategi pembelajaran untuk menghasilkan outcome pembelajaran yang berkualitas. Konsep literasi digital dalam setting Blended Learning yang dikembangkan secara proporsional dapat dipertimbangkan sebagai salah satu upaya dalam meningkatkan kualitas pembelajaran pada abad 21.Kata kunci: Blended Learning, literasi digital, pembelajaran abad 21.